Trading networks with frictions - Tamás Fleiner; Ravi Jagadeesan; Zsuzsanna Jankó; Alexander Teytelboym (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We show how frictions and continuous transfers jointly affect equilibria in a model of matching in trading networks. Our model incorporates distortionary frictions such as transaction taxes, bargaining costs, and incomplete markets. When contracts are fully substitutable for firms, competitive equilibria exist and coincide with outcomes that satisfy a cooperative stability property called trail stabity. In the presence of frictions, competitive equilibria might be neither stable nor (constrained) Pareto-efficient. In the absence of frictions, on the other hand, competitive equilibria are stable and in the core, even if utility is imperfectly transferable.
Keywords: C62; C78; D47; D51; D52; L14; 330; Trading networks; frictions; competitive equilibrium; matching with contracts; trail stabity; transaction taxes; commission